(untitled) (Mustansiria Dental Journal, 2024)
which are chemically—cured composite such as Two—past and No—mix systems in whicl the composite set by chemical reaction; Light—cured composite system, in whicl :composite set by light exposure; and Dual—cured composite system, by which th composite cured by chemical reaction and light exposure. Thus it is necessary tt .investigate and compare the commonly used composite bonding systems This study was aimed to determine and compare the shear bond and rebonc strength of: Two—past composite system (Concise, 3M, Unitek USA), No—mix composite ,system (Right—On, TP Orthodontics UK), Light—cured composite system (Transbond XT .)M Unitek USA), and Dual—cured composite system (Sono—Cem ESPE, Germany3 ,Fifty six upper premolars were divided into four groups of fourteen, each group mesh—backed metal advant edge brackets were bonded to the buccal surface ofthe teeth using one of the composite system according to the instruction of manufacturer. Then .bonded samples were thermocycled in an attempt to simulate oral circumstances The samples were subjected to shear force using the universal compression machine apparatus, then the results were recorded in Megapascal (Mpa). The remaining composite on the buccal surface of the tooth was removed by hand sealer and polished, a new bracket was bonded to the buccal surface of the tooth using the same type of composite system. The rebonded samples were tested under shear strength using the .universal compression machine apparatus and the results were again recorded in Mpa ,The data were statistically analyzed using descriptive analysis, ANOVA test .Dtu1can’s Multiple Range Test and Student’s t—test at p g 0.0l The results showed that the Concise had no significant higher bond shear strength than the Transbond and Sono—Cem composite systems, and there was signilicant increase bond strength of the Concise than the Right—On composite systems. Furthermore, there were no significant differences in bond shear strength among the Right—On, Transbond .and Sono—Cem composite systems